Improvement of Rhythmic Movement Skills of Grade I Students at SDN 1 Landasan Ulin Selatan Through the Problem Based Learning Model - Saputra, Gilang Akbar; Fauzan, Lazuardy Akbar; Suadmaji, Suadmaji (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This research aims to support the improvement of rhythmic movement skills of grade I students of SDN 1 Landasan Ulin Selatan through the application of the Problem Based Learning (PBL) model. This research is a Class Action Research (PTK) which is carried out in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects amounted to 25 students in grade I. In the learning process, students were given simple problems related to rhythmic movements, such as harmonizing body movements with musical rhythms, maintaining movement balance, and coordinating hand and foot movements in group activities. Students work collaboratively in small groups through motion demonstrations, visual media, and teacher guidance to solve a given movement problem. Data collection techniques are carried out through observation, practice tests of rhythmic movement skills, and documentation. The assessment of rhythmic movement skills is carried out based on several indicators, namely rhythmic accuracy, movement coordination, agility, cohesiveness, and student confidence. The data was analyzed using quantitative descriptive techniques by calculating the average score and percentage of learning completeness in each cycle. The results of the study showed a gradual improvement in students' rhythmic movement skills during the implementation of the Problem Based Learning model. In the pretest stage (pretest), the average score of students was 65 with a learning completion percentage of 32%. After the action in Cycle I, the average score increased to 74 with a completion percentage of 48%. In Cycle II, the average score increased again to 85 with a completion percentage of 84%. These findings show that the application of the Problem Based Learning model contributes positively to the improvement of rhythmic movement skills of grade I students of SDN 1 Landasan Ulin Selatan.